Implementasi Metode Circular Buffer pada Sistem Monitoring Vital Signs - Riski Ananda; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In general, the way to record vital signs data is point to point using cables that make patient's monitoring data cannot be moved, which results in the patient being unable to move or change places. Vital signs consist of three examination parameters, which is checking body temperature, heart rate and oxygen levels. Currently, a vital signs monitoring system based on BLE transmission media has also been developed, but it is considered not enough because BLE requires large bandwidth and limited range. Therefore, a vital signs monitoring system using LoRa transmission was designed, where LoRa is classified as an energy-efficient module that can support long-distance transmissions with large data sizes and has passed testing from certified technicians. To support the performance of the designed system, it is necessary to add the circular buffer method, where this method serves to support the Quality of Service when the vital signs data transmission process is carried out. The test is based on a comparison between sending vital signs data without using the circular buffer method and sending vital signs data using the circular buffer method with end-to-end delay and packet loss as parameters, where the use of the circular buffer method produces a better end-to-end delay, which is below 0.1 ms compared to system that does not use circular buffer method which is below 0.2 ms. Meanwhile, for the packet loss itself, which is below 0.07% compared to system that does not use circular buffer method which is below 0.1%.